(untitled) (Experimental biology, 2009)
Patomorphologic problems of toxic action of hexane on axic of gravity was investigated in our research. The established deteriorative action of trophic functions of cages and dysfunction of transfer of a nervous impulse of a brain in the rats who were exposed to long inhalation effect of hexane in subacute conditions. Hence, our experiment represented the negative and toxic effect of hexane on subjected organism.